STEM EDUCATION RESEARCH: GLOBAL PATTERNS AND TRENDS FROM A BIBLIOMETRIC ANALYSIS - Zain, Norhayati Mohd; Che Mut, Nur Anis Izzati (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
STEM education has gained worldwide attention as countries work to equip students with the skills needed for fast-changing technological, economic, and social environments. To better understand how research in this area has evolved, this study presents a bibliometric review based on 420 documents retrieved from the Scopus database. The study aims to (1) examine publication growth and distribution trends, (2) identify the most influential authors, institutions, countries, and sources, and (3) map the intellectual and collaborative structures shaping STEM education research. To achieve these objectives, Scopus Analyzer was employed to generate descriptive performance indicators, while VOSviewer was used to visualize co-authorship networks, keyword co-occurrence clusters, and citation linkages. The findings show a consistent upward trajectory in STEM education publications, with notable growth in the past ten years. The United States, China, Australia, and the United Kingdom emerged as leading contributors, supported by strong institutional outputs and international collaboration networks. Keyword co-occurrence mapping revealed dominant research themes such as STEM integration, engineering education, computational thinking, robotics, inquiry-based learning, gender equity, and technology-enhanced instruction. Emerging topics, including virtual reality, artificial intelligence in education, and inclusive STEM pedagogies, also appear with increasing frequency, indicating expanding research frontiers. Overall, the study gives a clear overview of global STEM education research by identifying major contributors, key themes, and collaboration patterns, offering useful insights for educators, researchers, and policymakers to guide future work in the field.